Use of soy massa as a food source in finishing lambs (Research, Society and Development, 2024)
The study aimed to evaluate the performance of lambs finished with two diet formulations, one using a commercial feed and the other using a soy co-product called soy mass. Forty-two castrated male lambs, mixed breed and aged between 8 and 10 months, were used. The design used was completely randomized with three replications of each treatment. The treatments were: Control (CON), without addition of co-product and soybean mass (MAS), with addition of co-product. Both diets were in the proportion roughage:concentrate (V:C) of 20-80%, where the roughage used was corn silage. Every 7 days all animals were weighed to follow the ADG and ECC and FAMACHA were measured. When they reached the established weight, they were transported to the slaughterhouse where the slaughter took place, after which the finish of each carcass was evaluated. For statistical analysis, Fisher's test was performed at a significance level of 5% for comparison between termination systems, in the SAS statistical program (v.9.1). The evaluations and average values of each treatment were then: FAMACHA CO 1.29; MS 1.42; ECC CO 2.32; MS 2.19; ADG CO 0.165g; MS 0.171g; CMS CO 67.97kg; MS 53.28kg; WeightQ CO 22.45kg; MS 21.23kg; yield CO 47.36%; MS 48.38% and CO finishing 3.67; MS 3.17. It was concluded that the addition of soy mass in the diet of lambs decreases the dry matter intake, however, it does not influence the finishing of the carcasses.